The Relationship of Postpartum Mother's Knowledge and Perineum Wound Care Behavior - Wulandari, Yunisa; Astuti, Dhesi Ari (Buletin Ilmu Kebidanan dan Keperawatan, 2024)
Postpartum infections still play a role as one of the leading causes of maternal death, especially in developing countries like Indonesia. The main factor causing infection during the postpartum period is poor care of the perineum. Mothers do not know enough about caring for perineal wounds, such as washing hands before cleaning genitalia and drying genitalia after defecating and urinating. The research aimed to determine the relationship between postpartum mothers' knowledge and perineal wound care behavior at TPMB Kuswatiningsih. This research method is quantitative research using a cross-sectional approach. The sample was taken using the accidental sampling method with 39 respondents. The tool in this research was a questionnaire. The statistical test used the Kendall Tau test with a p-value <0.05. The statistical test results obtained a p-value of p- value= .015 (p-value=<0.05) and a correlation coefficient value of 0.925, so it can be concluded that the relationship between the variable Knowledge of Postpartum Mothers and Perineal Wound Care Behavior is solid. The suggestion for TPMB Kuswatiningsih is that it is hoped that health workers will be more active in providing health education to the community, especially mothers, regarding postpartum care and perineal wound care.